Thermal Performance Evaluation of a Phase Change Material Based Heat Sink: A Numerical Study. (2016) - Thomas, Jesto; Srivatsa, P.V.S.S.; Krishnan, S. Ramesh; Baby, Rajesh
Abstract: This paper numerically investigates the thermal performance of a portable electronic device using PCM based heat sink. The phase change material used in the present study is n-eicosane with a melting point of 36.5 0 C. Considering the current trend in portable electronic devices, a group of smart phones were taken and an average dimension was selected for designing a PCM based heat sink. A constant heat flux is provided at the heat sink bottom for simulating the heat generation by the electronic circuit board. Numerical analysis were performed for a constant heat input of 4 to 6 W in steps of 0.5 W on this heat sink to study its effect in conjunction with PCM in the efficient cooling of these devices. The effect of natural convention within the melt is also discussed in this paper. All the numerical computations were performed using ANSYS FLUENT 14.0.